2009
DOI: 10.1002/jat.1494
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of aluminum nanoparticles with human epidermal keratinocytes

Abstract: Aluminum nanoparticles (Al NP) have been used in applications as diverse as drug delivery, material surface coatings and an ingredient for solid rocket fuel in military explosives and artillery. Although Al NP are used in many civilian and military applications, the health and safety implications of these nanosize particles are not known. To understand the interactions and biological activity of Al NP in human cells, cultured human neonatal epidermal keratinocytes (HEK) were exposed for 24 h to 50 and 80 nm Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 27 publications
2
42
1
1
Order By: Relevance
“…This might be due to a false positive reaction in which MTT was converted to formazan in the absence of cells. However, these small interferences did not result in further increases in cell viability with increasing concentration (false viability), which is in contrast to previous reported data for other types of nanomaterials [19,20]. These data prove that these viability endpoints are suitable for the intended purpose.…”
Section: Cytocompatibility Studiescontrasting
confidence: 62%
See 1 more Smart Citation
“…This might be due to a false positive reaction in which MTT was converted to formazan in the absence of cells. However, these small interferences did not result in further increases in cell viability with increasing concentration (false viability), which is in contrast to previous reported data for other types of nanomaterials [19,20]. These data prove that these viability endpoints are suitable for the intended purpose.…”
Section: Cytocompatibility Studiescontrasting
confidence: 62%
“…To determine whether the NVs interact with the viability assays, UV-visible absorbance measurements were carried out [19,20]. NVs at 100 μM were suspended in DMEM medium (without FBS and phenol red) containing MTT (0.5 mg/ml) or NR (50 μg/ml) dyes.…”
Section: Cell Culturesmentioning
confidence: 99%
“…It is well known that these cells under normal physiological conditions, due to their protective role in the skin, do not possess the ability to internalise any foreign body materials. Anyway some reports show that nanosized particles, such as nickel oxide, aluminium and silver nanoparticles are internalised by these cells [26][27][28], but it has never been reported that carbonaceous nanoparticles can be spontaneously up taken by keratinocytes. Unexpectedly, we observed that normal keratinocytes in vitro are able to take up spontaneously diesel exhaust nanoparticles after 24 h exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Im Sinne der Vorsorge werden auch andere Nanomaterialien wie CNTs, [85] Silbernanopartikel, [38,86] Quantenpunkte [36,87,88] oder Aluminium [89] auf ihre mögliche toxische Wirkung überprüft, wobei immer zu beachten ist, ob diese Materialien auch die Hornschicht des Stratum corneum in ausreichender Weise penetrieren können. Vermehrt werden Fullerene (C 60 ) als Radikalfänger in Kosmetika beigemischt (Vitamin C60 BioResearch Corporation; siehe http://www.vc60.com/).…”
Section: Wirkung Von Nanoobjekten Auf Die Hautunclassified